Clinical Validity of hearScreen™ Smartphone Hearing Screening for School Children. Issue 1 (January 2016) - Mahomed-Asmail, Faheema; Swanepoel, De Wet; Eikelboom, Robert H.; Myburgh, Hermanus C.; Hall, James
Abstract : Objectives: The study aimed to determine the validity of a smartphone hearing screening technology (hearScreen™) compared with conventional screening audiometry in terms of (1) sensitivity and specificity, (2) referral rate, and (3) test time. Design: One thousand and seventy school-age children in grades 1 to 3 (8 ± 1.1 average years) were recruited from five public schools. Children were screened twice, once using conventional audiometry and once with the smartphone hearing screening. Screening was conducted in a counterbalanced sequence, alternating initial screen between conventional or smartphone hearing screening. Results: No statistically significant difference in performance between techniques was noted, with smartphone screening demonstrating equivalent sensitivity (75.0%) and specificity (98.5%) to conventional screening audiometry. While referral rates were lower with the smartphone screening (3.2 vs. 4.6%), it was not significantly different ( p > 0.05). Smartphone screening (hearScreen™) was 12.3% faster than conventional screening. Conclusion: Smartphone hearing screening using the hearScreen™ application is accurate and time efficient. Abstract : School-entry hearing screening is the first point of access for screening in most developing countries and even in some developed countries. However, effective implementation of school-based hearing screening presents a number of significant challenges. A recent report of a smartphone hearing screening application, hearScreen™, has demonstrated promise to address many of these challenges (Swanepoel et al. 2014). This study aimed to determine the clinical validity of hearScreenTM compared to conventional screening audiometry. Our results suggest that Smartphone hearing screening (hearScreenTM) is an accurate tool that is time-efficient, inexpensive, and easy to use.